Exploring the underlying mechanisms of Ashitaba in the management of non-alcoholic fatty liver disease by integrating the analysis of transcriptomics and metabolomics - Yang, Huan; Li, Yunshan; Xu, Weihong; Liu, Wenjuan; Xie, Ying (Frontiers in Medicine, 2023)
Ashitaba seems to improve glucose intolerance and decrease triglyceride (TG) and total cholesterol (TC), which contribute to the development of non-alcoholic fatty liver disease (NAFLD). However, it remains to be explored the mechanism of Ashitaba in managing NAFLD. We determined the impact of Ashitaba on NAFLD, particularly its underlying mechanisms at the bioinformatic level. The established NAFLD mouse model was treated with or without Ashitaba, and the underlying mechanism was explored using transcriptomics paired with metabolomics. Ashitaba reduced obesity and liver steatosis in NAFLD mice. It identified 429 differentially expressed genes (DEGs) and verified 45 differential metabolites, especially those that alleviate NAFLD via the FXR signaling pathway. Our data may provide insight into the therapeutic impact of Ashitaba in the management of NAFLD and may be useful in clinical interventions for NAFLD.